Climate Change and Water Resources Planning, Development, and Management in Zimbabwe : An Issues Paper - World Bank (Washington, DC, 2016)
This Issues Paper, requested by the former Ministry of Water Resources Development and Management as a recommendation of the National Water Policy (NWP), will contribute to the National Climate Change Response Strategy (NCCRS) by examining opportunities for adaptation to climate change in the water resources sector, using both structural and non-structural measures. It uses models to provide preliminary estimates of the possible impacts of climate change in 2050 and 2080 on these water resources. A number of opportunities to adapt to these impacts are discussed. Many of these adaptation opportunities constitute no-regrets actions, in that they are actions that are worth undertaking in their own right, irrespective of the severity of impacts from climate change.